2024
DOI: 10.3389/fmicb.2023.1287701
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of soil organic matter under varying agricultural management systems in Ukraine

Lyudmyla Symochko,
Olena Demyanyuk,
Vlad Crisan
et al.

Abstract: IntroductionThis paper presents comparative studies on the content and structure of organic matter (OM) and the activity of microbiological cellulose destruction in three types of Ukrainian soils intensively used in agricultural production.MethodsThe highest content of humus in the arable layer (4.9%), OM (410 t ha−1), and total carbon (30.9 mg C g−1 soil) was determined in chernic phaeozems, which is 2.2–2.5 times higher than in albic retisols. The soil of natural ecosystems is characterised by a high content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Specifically, in agroecosystems where SMS was applied, the soil exhibited a higher organic matter content of 49.00% compared to 34.31% for peat. This disparity is expected to positively impact the soil microbiome, fostering conducive conditions for blueberry growth and fruiting [47][48][49]. Furthermore, Lipiec et al [50] confirmed that the application of spent mushroom substrate, particularly over the long term, augmented the organic matter content within the soil.…”
Section: Additive To the Soil For Blueberry Cultivationmentioning
confidence: 97%
“…Specifically, in agroecosystems where SMS was applied, the soil exhibited a higher organic matter content of 49.00% compared to 34.31% for peat. This disparity is expected to positively impact the soil microbiome, fostering conducive conditions for blueberry growth and fruiting [47][48][49]. Furthermore, Lipiec et al [50] confirmed that the application of spent mushroom substrate, particularly over the long term, augmented the organic matter content within the soil.…”
Section: Additive To the Soil For Blueberry Cultivationmentioning
confidence: 97%
“…Organic agriculture comprises "management procedures that work with natural processes to conserve all resources, minimize waste and environmental impact and promote agroecosystem resilience" (Rees et al, 2018;Symochko et al, 2024). The Himalayan Foothills, characterized by its diverse topography and fragile ecosystem, presents a compelling setting for investigating the impact of organic farming on agricultural sustainability.…”
Section: Introductionmentioning
confidence: 99%